2021
DOI: 10.1111/cen.14651
|View full text |Cite
|
Sign up to set email alerts
|

The association between adrenal adenoma size, autonomous cortisol secretion and metabolic derangements

Abstract: Objective Autonomous cortisol secretion (ACS) is common in patients with adrenal incidentalomas (AI). ACS is associated with increased cardiovascular morbidity and mortality. Data regarding the association between radiological characteristics of adrenal adenomas, their hormonal functionality and metabolic outcomes, are scarce and inconclusive. In this study, we aim to delineate the association between radiological characteristics of AI, ACS and metabolic status. Methods A cross‐sectional study of 77 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…A prior cross-sectional study reported that a plain HU of ≥18.5 on non-contrast CT scans was a significant radiological parameter that could help detect functioning AI [ 8 ], while our study determined that patients with HU < 10 on plain CT scans have a probability of the mass being functioning 2.47 times that of patients with HU ≥ 10. Similar to our study, a previous report on 77 patients stated that a greater mass size of AI was significantly related to functioning AI, particularly the ACS subtype [ 11 ]. That study, however, did not specify the cut-off nodule size associated with a significantly increased risk of a functioning AI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A prior cross-sectional study reported that a plain HU of ≥18.5 on non-contrast CT scans was a significant radiological parameter that could help detect functioning AI [ 8 ], while our study determined that patients with HU < 10 on plain CT scans have a probability of the mass being functioning 2.47 times that of patients with HU ≥ 10. Similar to our study, a previous report on 77 patients stated that a greater mass size of AI was significantly related to functioning AI, particularly the ACS subtype [ 11 ]. That study, however, did not specify the cut-off nodule size associated with a significantly increased risk of a functioning AI.…”
Section: Discussionsupporting
confidence: 91%
“…In categorizing mass size, we used a standard cut-off of 4 cm because that value is widely used in the evaluation of the malignancy of a mass, and hence to determine the appropriate management for AI patients. Most previous reports have stated that there is a correlation between functioning AI and larger mass size [ 11 , 12 ]. For example, Barzon et al stated that masses of >3 cm are linked to functioning AI [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal glands control a variety of vital physiological processes with endocrine secretory function 4 . Adrenal adenomas with abnormal adrenal hormone production, such as primary aldosteronism and hypercortisolism, are closely relevant to dysregulated blood pressure, blood lipids, and blood glucose 5–8 . Adrenal morphological abnormity without aberrant adrenal functions, for example adrenal incidentaloma or adrenal hypertrophy, was regarded as lacking clinical significance for a long time.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Adrenal adenomas with abnormal adrenal hormone production, such as primary aldosteronism and hypercortisolism, are closely relevant to dysregulated blood pressure, blood lipids, and blood glucose. 5 , 6 , 7 , 8 Adrenal morphological abnormity without aberrant adrenal functions, for example adrenal incidentaloma or adrenal hypertrophy, was regarded as lacking clinical significance for a long time. The significance of adrenal morphology to metabolic profiles has been unrecognized to some extent, until the last decades, evidence is accumulating on the association between adrenal size and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%